2014
DOI: 10.4081/bam.2014.3.173
|View full text |Cite
|
Sign up to set email alerts
|

The Ubr2 gene is expressed in skeletal muscle atrophying as a result of hind limb suspension, but not Merg1a expression alone

Abstract: Skeletal muscle (SKM) atrophy is a potentially debilitating condition induced by muscle disuse, denervation, many disease states, and aging. The ubiquitin proteasome pathway (UPP) contributes greatly to the protein loss suffered in muscle atrophy. The MERG1a K + channel is known to induce UPP activity and atrophy in SKM. It has been further demonstrated that the mouse ether-a-gogo-related gene (Merg)1a channel modulates expression of MURF1, an E3 ligase component of the UPP, while it does not affect expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the expression of Merg1a did not affect expression nor abundance of the UPP E3 ligase atrophy marker, Mafbx/ATROGIN1. 30 More work is needed to determine the role that the ERG1A K + channel plays in skeletal muscle physiology and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of Merg1a did not affect expression nor abundance of the UPP E3 ligase atrophy marker, Mafbx/ATROGIN1. 30 More work is needed to determine the role that the ERG1A K + channel plays in skeletal muscle physiology and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…ERG1A is up-regulated in skeletal muscle undergoing atrophy as a consequence of unloading, cancer cachexia and denervation (Zampieri et. al., 2021;Wang et al, 2006;Hockerman et al, 2013;Pond et al, 2014). It is likely, therefore, that some factor common to these conditions induces expression of ERG1A.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2006); 2) atrophy is induced in mouse muscle by ectopic expression of wild type Erg1a (Wang et. al., 2006); and 3) abundance of the UPP E3 ubiquitin ligase MuRF1 (but not ATROGIN1) and overall UPP activity are increased in mouse skeletal muscle by ectopic overexpression of Erg1a (Hockerman et al, 2014; Pond et al, 2013; Wang et al, 2006). Further, we have shown that the ERG1A K + channel protein is expressed at low abundance in C 2 C 12 myotubes and that augmentation of its expression in these cells, as in mouse skeletal muscle, will induce a decrease in cell size (i.e., myotube area) and an increase in the abundance of the E3 ubiquitin ligase MuRF1, but not the E3 ligase ATROGIN1 (Whitmore et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While not all genes identified by the pathway analysis currently have a well‐defined role in skeletal muscle (i.e., BIRC4 or USP11) many including USP19, USP2, and UBR2 are associated with skeletal muscle dysfunction (Wing ; Hockerman et al. ). Together with a decrease in the MAPK/ERK signaling pathway, which responds to cellular stress (Kim and Choi ), is consistent with a decreased need for the clearance of damaged proteins in young ET individuals.…”
Section: Discussionmentioning
confidence: 99%